Bali dalam Novel Liebe und Tod auf Bali Karya Penulis Wanita Jerman Vicky Baum - Lilawati Kurnia (HISKI, 2005)
Liebe und Tod auf Bali, or Love and Death in Bali is the masterpiece of Vicky Baum, a female author from Germany. A Balinese Romeo and Juliet, it tells the story of a love forbidden because of caste difference. The background for this story is the colonial East Indies or Indonesia during its occupation by the Dutch. Baum showed her sympathy with the Balinese through her detailed ethnographical story of the people and their traditions. She wanted to argue the Balinese were still in a medieval state and needed to be brought into Western civilization, which was more modern and advanced. In doing so, Baum was adopting the perspective of the colonial, and once again the power of Western civilization won.Kata kunci: citra, etnosentrisme, eksotisme, etnografis, das Fremde, das Eigene.